A 22-Years-Old Male with Tuberculoma of the Brain and Spinal Cord with Miliary Tuberculosis - Rosinondang Deolita Simamora; Retnaningsih; Elta Diah Pasmanasari; Hexanto Muhartomo (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2025)
Background: Tuberculosis (TB) remains a significant health issue in Indonesia. Central nervous system (CNS) tuberculoma is one of the extrapulmonary TB diseases and accounts for approximately 1% of all cases. The emergence of this disease is primarily associated with a weakened immune system. However, several other factors, such as comorbidities, a history of inadequate TB treatment, and poor nutrition, also play a role in the development of tuberculoma. Case: A 22-year-old male complained of weakness in all four limbs for the past month, accompanied by tingling and numbness from both feet up to the T10-11 dermatome level. The patient has a history of seizures from one year ago, interrupted treatment for military tuberculosis, and malnutrition. An MRI of the head and whole spine with contrast revealed tuberculomas. The patient was treated with medication, including intravenous dexamethasone 5 mg every 8 hours, oral phenytoin 200 mg every 24 hours, and anti-tuberculosis therapy. Discussion: Tuberculoma in the central nervous system is rare, especially multiple tuberculomas co-occurring in the brain and spinal cord. MRI is a sensitive tool for diagnosing tuberculomas, characterized by the presence of a target sign. The combination of corticosteroids, antiepileptic drugs, and an entire course of anti-tuberculosis medications aims to address both the immediate neurological symptoms and the underlying infection. Conclusion: TB can present as lesions in the brain and spinal cord, requiring the ability to correlate clinical manifestations and radiological features to establish a diagnosis and necessitating adequate therapy.